Analysis of compressive strength of occlusal splints manufactured with three liquid resins at three angles of orientation on 3D printer (Research, Society and Development, 2022)
The aim of this study is to analyze the compressive strength of occlusal splints manufactured with three different liquid resins in a 3D printer and in three angles of orientation. The resins used here are (n=12): Resilab Clear (Wilcos do Brasil, Petrópolis, RJ, Brazil), Prizma Smart Print Bio (Makertech Labs, Tatuí, SP, Brazil), and Cosmos Splint (Yller Biomateriais, Pelotas, RS, Brazil); each resin group are divided into three subgroups according to orientation of manufacture: 0, 45 and 90 degrees. A dental manikin was scanned and the file was used to manufacture a steel hemiarch model. This model was used to design the occlusal splints and as a basis for the tests. The splints were designed with flat occlusal surface and minimum thickness of 2 mm. The compressive test was performed with constant force of 200N, velocity of 0.5 mm/min, along the entire occlusal surface until fracture. Results show no difference between the resins, regardless of orientation of manufacture. The orientation showed no intragroup effect for resins Prizma Smart Print Bio and Resilab Clear; the resin Cosmos showed larger compressive strength for the samples manufactured at 45 degrees than at 0 degree. The 90-degree samples were intermediary and showed no difference from other angles. This study shows that the three resins had similar behavior in terms of compressive strength, except for the intragroup effect of orientation of Cosmos Splint resin, where plates manufactured at 0 degree performed worse than those at 45 degrees.